Dietary adequacy and parenting practices associated with toddler stunting in UPT Puskesmas Koppe - Valentino , A. Ayus; Nurlianih, Andi (Priviet Social Sciences Journal, 2025)
Stunting is a chronic nutritional problem that remains a serious concern in Indonesia, including Bone Regency. This condition is associated with long-term undernutrition, maternal knowledge of nutrition, and suboptimal caregiving practices and affects physical growth, cognitive development, productivity, and the risk of disease later in life. This study aimed to analyze the relationship between dietary adequacy, maternal nutrition knowledge, and caregiving practices with stunting among toddlers in the service area of UPT Puskesmas Koppe and to identify the dominant factors influencing it. An analytic quantitative study with a cross-sectional design was conducted in the UPT Puskesmas Koppe service area. A total of 43 respondents were selected using purposive sampling based on inclusion and exclusion criteria. Data were collected through interviews using questionnaires and a Food Frequency Questionnaire (FFQ) to measure dietary adequacy, maternal knowledge, and caregiving practices. Data analysis included univariate, bivariate (chi-square test), and multivariate (logistic regression) analyses. The prevalence of stunting in toddlers was 39.5%. There was a significant association between dietary adequacy and stunting (p=0.000), in which all toddlers with inadequate nutrition were stunted. Caregiving practices were also significantly associated with stunting (p=0.024), with a 6.75-times higher risk among toddlers receiving suboptimal care. Maternal knowledge was not significantly associated with stunting (P =0.783). Logistic regression confirmed that dietary adequacy was the most important factor influencing stunting. Adequate nutrition and optimal care are crucial for preventing stunting. Interventions should prioritize improving access to and the quality of nutrition, as well as strengthening caregiving practices at the household level through support from health workers.